2009
DOI: 10.1100/tsw.2009.90
|View full text |Cite
|
Sign up to set email alerts
|

HIV-Envelope–Dependent Cell-Cell Fusion: Quantitative Studies

Abstract: Interaction in vitro between cells infected with human immunodeficiency virus (HIV) and surrounding, uninfected, target cells often leads to cell fusion and the formation of multinucleated cells, called syncytia. The presence in HIV-infected individuals of virus strains able to induce syncytia in cultures of T cells is associated with disease progression and AIDS. Even in the asymptomatic stage of infection, multinucleated cells have been observed in different organs, indicating that fused cells may be generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 97 publications
(85 reference statements)
0
13
0
Order By: Relevance
“…The same phenomenon was found to occur in the case of the enJSRV env genes [22]. In the case of several enveloped viruses, the Env protein synthesized by infected cells and exposed at their surface can confer on them the ability to fuse with neighbouring uninfected cells that express the appropriate receptor, resulting in the formation of multinucleated giant cells called syncytia (figure 2b) [31]. In this context, several placentaspecific genes encoding fusogenic Env proteins co-opted from members of distinct ERV families have been identified within the genome of various mammalian species.…”
Section: The Retroviral Envelope Glycoproteinmentioning
confidence: 74%
“…The same phenomenon was found to occur in the case of the enJSRV env genes [22]. In the case of several enveloped viruses, the Env protein synthesized by infected cells and exposed at their surface can confer on them the ability to fuse with neighbouring uninfected cells that express the appropriate receptor, resulting in the formation of multinucleated giant cells called syncytia (figure 2b) [31]. In this context, several placentaspecific genes encoding fusogenic Env proteins co-opted from members of distinct ERV families have been identified within the genome of various mammalian species.…”
Section: The Retroviral Envelope Glycoproteinmentioning
confidence: 74%
“…The results of those immunizations were basically negative despite the presentation of the ELDKWAS (or some longer sequence) peptide on various vectors and the inclusion of a fusion peptide sequence [45] and lipids [46] as parts of the viral structures to optimize the 2F5 antigenic function (see [37] for exhaustive critical analysis of this item). Using a cell-cell fusion system, which was proven to be highly sensitive to inhibitors in our previous experiments [31][32][33][34][35] against 2F5 in this study, we found that mouse antiserum to the both the linear and constrained peptides did not affect fusion while the rabbit antiserum to the linear but not to the constrained peptide decreased fusion by approximately 50% and to 20% at 1:10 and 1:100 dilutions, respectively. Inhibition by mAb 2F5 was not observed in the presence of the 15-mer ELDKWAS-containing peptide competitor of the epitope (Fig.…”
Section: Immunogenic Potential Of the Described Linear And Constrainementioning
confidence: 79%
“…The cell-cell fusion protocol developed by Huerta et al [31] and subsequently extensively employed by Huerta et al [32], López-Balderas et al [33], Huerta et al [34], Rivera-Toledo et al [35] was used in these experiments to test the anti-mimotope serum antibodies. The protocol involves labeling fusion partner cells with the fluorescent carbocyanines DiI and DiO (Molecular Probes).…”
Section: Cell Culture and Cell-cell Fusion Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…The life cycle of enveloped viruses necessitates interaction and fusion of the viral lipid envelope with host-cell membranes for virus entry, intracellular trafficking of viral-envelope proteins and viral egress [13]. The functional significance of syncytia in viral pathology is not fully understood but it is likely that they facilitate cellcell spread of virus and may deplete large populations of susceptible cells [15]. In addition, viral-coat proteins can induce the formation of multinucleated syncytia, where a virus-infected cell fuses with uninfected cells.…”
Section: Virus Host-cell Interactionsmentioning
confidence: 99%